KINERJA TUTOR DALAM PEMBELAJARAN PENDIDIKAN KESETARAAN PAKET C DI SATUAN PENDIDIKAN NON FORMAL SANGGAR KEGIATAN BELAJAR (SPNF SKB) KOTA PEKANBARU - Lumbanraja, Erwina Mariana; Jas, Jaspar; Maemunaty, Titi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study examines the performance of tutors in the equivalencyeducation package C in the Non-Formal Education Unit of the Learning Activity Center(SPNF SKB) Pekanbaru City. This research uses a descriptive qualitative approach.The research subjects in this study were 4 (four) people. Data collection was done bymeans of observation, documentation, interviews. Data analysis was performed bymeans of data collection, data reduction, data display, and conclusion drawing /verifying. The results showed: 1) Planning in learning before the teaching and learningprocess took place was not good, 2) Implementation of learning was done well, 3)Assessment / evaluation The evaluation stage in learning was done well.Key Word: Tutor Performance, Learning